5
$\begingroup$

Question is like in title:

For positive integer $n$ I want to construct a polynomial $w(x)$ of degree $n$ with integer coefficients such that there exist $a_1<a_2<\cdots<a_n$ (integer numbers) satisfying $w(a_1)=w(a_2)=\cdots=w(a_n)=1$ and $b_1<b_2<\cdots<b_n$ (also integer numbers) satisfying $w(b_1)=w(b_2)=\cdots=w(b_n)=-1$.

I am not sure if such polynomial even exists for every $n$.

EDIT: $a_i, b_i$ are not predetermined, as someone mentioned in a comment.

$\endgroup$
10
$\begingroup$

This is not possible for $n>3$. In fact, it is not possible to find a degree-$n$ polynomial $w(x)$ which has $n$ different integer roots of $w(x)=1$ and even one integer root (say $b$) of $w(x)=-1$. This is because, if $a_1,...,a_n$ are the roots of $w(x)=1$, $w(x)-1=c(x-a_1)...(x-a_n)$, where $c$ is an integer. Thus $w(b)-1$ is $c$ times a product of $n$ different integers, and since at most two of these can be $\pm 1$, and all others have absolute value at least $2$, if $n>3$ then $w(b)-1$ can't equal $-2$ -- it must have absolute value at least $2^{n-2}$.

[edit] In fact what you asked for is not possible for $n=3$ either. For $w(b)-1=-2$ to have a solution we must have $(b-a_1)(b-a_2)(b-a_3)=-2$ so the three terms are $-1,+1,+2$. But if those are the three terms, then the order of them is determined, so there is at most one solution for $b.$ It is possible for $n=2$: take $w(x)=x^2-3x+1$. Then $w(x)=1$ has two solutions $x=0,3$ and $w(x)=-1$ has two solutions $x=1,2$.

$\endgroup$
  • $\begingroup$ Great answer, thanks! $\endgroup$ – Shingle Feb 21 '17 at 12:01
  • $\begingroup$ Nice argument (+1). $\endgroup$ – lulu Feb 21 '17 at 12:01
3
$\begingroup$

$\newcommand{\Size}[1]{\left\lvert #1 \right\rvert}$$\newcommand{\Set}[1]{\left\{ #1 \right\}}$Just to complement the excellent answer (+1), if $n = 1$ you have $$ w(x) = C (x - a_{1}) + 1, $$ and $$w(b_{1}) = C (b_{1} - a_{1}) = -2,$$ so there is a solution iff $b_{1} - a_{1} \in \Set{\pm 1, \pm 2}$.

If $n = 2$ you have $$ w(x) = C (x - a_{1})(x - a_{2}) + 1, $$ and need $$ C (b_{1} - a_{1})(b_{1} - a_{2}) = -2 = C (b_{2} - a_{1})(b_{2} - a_{2}), $$ and there are solutions for instance for $$\tag1\label1 b_{1} = a_{1} + 1 = a_{2} - 2, $$ so that $a_{2} = a_{1} + 3$ and $$\tag2\label2 b_{2} = a_{1} + 2 = a_{2} - 1, $$ say $a_{1} = 0, a_{2} = 3, b_{1} = 1, b_{2} = 2$, and then $C = 1$.

Actually, for the case $n = 2$ we have $$ a_{2} - a_{1} = \Size{a_{2} - a_{1}} \le \Size{b_{1} - a_{1}} + \Size{b_{1} - a_{2}} \le 3, $$ so I think the general conditions for the existence of a solution are indeed $\eqref1$ and $\eqref2$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.